EGGS, LARVAE AND JUVENILES OF FISHES FROM INDIAN WATERS XI. Further Observations on the Genus Auxis Cuvier - Jones, S (Indian Journal of Fisheries, 2011)
Two species are known under the genus Auxis and both have been recordedfrom Indian coasts (Jones, .1958; Jones and Silas, 1960). Of these the shortcorseletted form, A. (hazard, is found in all the warm seas while the longcorseletted form A. thynnoides is considered to be confined to the Indo-Pacific. However, Matsumoto (1959) has expressed the view that the speciesoccurring on the Atlantic coast of America has a long corselet, which ifconfirmed, would change considerably our distributional concept of thetwo species. While there is no doubt about the existence of two speciesof Auxis in the Indo-Pacific, it is obvious that thek nomenclature requiresfurther elucidation (Jones and Silas, MS.).